2004
DOI: 10.1111/j.1365-2958.2004.04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the psa permease complex of Streptococcus pneumoniae

Abstract: SummaryThe psaBCA locus of Streptococcus pneumoniae encodes a putative ABC Mn 2+ + + + -permease complex. Downstream of the operon is psaD , which may be cotranscribed and encodes a thiol peroxidase. Previously, there has been discordance concerning the phenotypic impact of mutations in the psa locus, resolution of which has been complicated by differences in mutant construction and the possibility of polar effects. Here, we constructed unmarked, in frame However, we found that deleting psaB resulted in decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
167
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(180 citation statements)
references
References 36 publications
13
167
0
Order By: Relevance
“…A previous study from our group showed that the high affinity manganese transporter, SsaB, is essential for O 2 tolerance and endocarditis virulence in S. sanguinis (26). This mirrored earlier findings showing that orthologs of this transporter are essential for endocarditis caused by other oral streptococci (29,30) for pneumonia, bacteremia, and otitis media caused by Streptococcus pneumoniae (31)(32)(33)(34), for bacteremia caused by S. pyogenes (35), and for mastitis caused by Streptococcus uberis (36). It is known that Mn II contributes to O 2 tolerance in part by serving as a cofactor for the superoxide dismutase SodA.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study from our group showed that the high affinity manganese transporter, SsaB, is essential for O 2 tolerance and endocarditis virulence in S. sanguinis (26). This mirrored earlier findings showing that orthologs of this transporter are essential for endocarditis caused by other oral streptococci (29,30) for pneumonia, bacteremia, and otitis media caused by Streptococcus pneumoniae (31)(32)(33)(34), for bacteremia caused by S. pyogenes (35), and for mastitis caused by Streptococcus uberis (36). It is known that Mn II contributes to O 2 tolerance in part by serving as a cofactor for the superoxide dismutase SodA.…”
Section: Discussionsupporting
confidence: 75%
“…PsaA is a metal-binding lipoprotein with specificity for Mn 2+ , and possibly also for Zn 2+ (Dintilhac et al, 1997;Lawrence et al, 1998). It has also been shown that mutations in psaA have pleiotropic effects on various pneumococcal functions, including resistance to oxidative stress, adherence and virulence (Berry & Paton, 1996;Claverys et al, 1999;Novak et al, 1998;Tseng et al, 2002;McAllister et al, 2004). In addition, immunization with PsaA has been found to confer significant levels of protection against nasopharyngeal carriage (Briles, 2000a, b;Palaniappan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Three enzymes are involved primarily in the production of hydrogen peroxide during pneumococcal metabolism; pyruvate oxidase encoded by spxB, lactate oxidase encoded by lox, which converts lactate to pyruvate and carbamoyl phosphate synthase encoded by carB [52][53][54]. S. pneumoniae has evolved to cope with the resultant oxidative stress in several ways; sodA encodes the manganese superoxide dismutase (MnSOD) that removes superoxide, the NADH oxidase encoded by nox removes O2 to H2O, preventing its conversion to superoxide, SpxB enables acetyl phosphate to be converted to adenosine triphosphate (ATP), preventing ATP depletion during oxidative stress, psaA encodes a manganese permease and psaD a putative glutathione reductase, which together alter redox status and limit hydrogen peroxide production via SpxB, while AdhC is an alcohol dehydrogenase that generates the reduced glutathione required for PsaD [55][56][57][58][59][60]. Other factors contributing to resistance to oxidative stress include the heat shock-induced protease HtrA, a putative alkylhydroperoxidase AhpD, the ClpP protease, a putative transcriptional regulator Rgg and a putative thioredoxin-like protein TlpA [61][62][63][64][65].…”
Section: Microbicidal Mechanisms By Which Macrophages Kill S Pneumoniaementioning
confidence: 99%